Obesity prevention programs and policies: Practitioner and policy‐maker perceptions of feasibility and effectiveness. (13th May 2013) - Cleland, Verity; McNeilly, Briohny; Crawford, David; Ball, Kylie
<x xml:space="preserve">Abstract</x> Objectives The aims of this study were 1 to map obesity prevention activity being implemented by government, non‐government, and community‐based organizations; 2 to determine practitioner and policy‐maker perceptions of the feasibility and effectiveness of a range of evidence‐based obesity prevention strategies; and 3 to determine practitioner and policy‐maker perceptions of preferred settings for obesity prevention strategies. Design and Methods This study involved a cross‐sectional survey of 304 public health practitioners and policy‐makers from government, non‐government, and community organizations across Victoria, Australia. Participants reported their organizations' current obesity prevention programs and policies, their own perceptions of the feasibility and effectiveness of strategies to prevent obesity and their preferred settings for obesity prevention. Results Thirty‐nine percent had an obesity prevention policy, and 92% were implementing obesity prevention programs. The most common programs focused on education, skill‐building, and increasing access to healthy eating/physical activity opportunities. School curriculum‐based initiatives, social support for physical activity, and family‐based programs were considered the most effective strategies, whereas curriculum‐based initiatives, active after‐school programs, and providing access to and information about physical activity facilities were deemed the most feasible strategies. Schools were generally perceived as the most preferred setting for obesity prevention. Conclusion Many organizations had obesity prevention programs, but far fewer had obesity prevention policies. Current strategies and those considered feasible and effective are often mismatched with the empirical literature. Systems to ensure better alignment between researchers, practitioners, and policy‐makers, and identifying effective methods of translating empirical evidence into practice and policy are required.